2021
DOI: 10.48550/arxiv.2109.03875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative central limit theorems for the parabolic Anderson model driven by colored noises

Abstract: In this paper, we study the spatial averages of the solution to the parabolic Anderson model driven by a space-time Gaussian homogeneous noise that is colored in time and space. We establish quantitative central limit theorems (CLT) of this spatial statistics under some mild assumptions, by using the Malliavin-Stein approach. The highlight of this paper is the obtention of rate of convergence in the colored-in-time setting, where one can not use Itô's calculus due to the lack of martingale structure. In partic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The method of [26] uses the multivariate chaotic central limit theorem, which yields the normal approximation, but does not give the rate of the convergence. This rate was obtained in the recent preprint [24], where it was shown that d T V ≤ CR −d/2 in case (a) and d T V ≤ CR −β/2 in case (b), using a different method based on an improved version of the second-order Gaussian Poincaré inequality due to [28], which was used for the first time in this context in [5]. In addition, [24] considers the more difficult case (c) of the fractional noise in space with index H < 1/2 (in dimension d = 1), which is also fractional in time with index H 0 > 1/2 satisfying H 0 + H > 3/4.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…The method of [26] uses the multivariate chaotic central limit theorem, which yields the normal approximation, but does not give the rate of the convergence. This rate was obtained in the recent preprint [24], where it was shown that d T V ≤ CR −d/2 in case (a) and d T V ≤ CR −β/2 in case (b), using a different method based on an improved version of the second-order Gaussian Poincaré inequality due to [28], which was used for the first time in this context in [5]. In addition, [24] considers the more difficult case (c) of the fractional noise in space with index H < 1/2 (in dimension d = 1), which is also fractional in time with index H 0 > 1/2 satisfying H 0 + H > 3/4.…”
Section: Introductionmentioning
confidence: 74%
“…This rate was obtained in the recent preprint [24], where it was shown that d T V ≤ CR −d/2 in case (a) and d T V ≤ CR −β/2 in case (b), using a different method based on an improved version of the second-order Gaussian Poincaré inequality due to [28], which was used for the first time in this context in [5]. In addition, [24] considers the more difficult case (c) of the fractional noise in space with index H < 1/2 (in dimension d = 1), which is also fractional in time with index H 0 > 1/2 satisfying H 0 + H > 3/4. In this case, the authors discovered the surprising rates σ 2 R (t) ∼ CR and d T V ≤ CR −1/2 , which show that once we descend below the value 1/2, the spatial index H does not have any impact on the rates in the QCLT.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The same problem for the fractional heat equation (in which the Laplacian is replaced by its fractional power) has been considered in [1]. The case of the parabolic Anderson model driven by a Gaussian noise colored in time was treated in [26,25], and the same model with rough noise in space appeared in [24].…”
Section: Introductionmentioning
confidence: 99%